(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Part-of-speech (POS) tagging is a foundational technique in natural language processing that involves assigning grammatical categories such as nouns, verbs, adjectives, and adverbs to every word in a text. This process enables machines to understand language structure, support linguistic analysis, and enhance various AI applications. POS tagging is essential for information extraction, machine translation, text mining, sentiment analysis, and speech recognition. Modern tagging methods combine rule-based, statistical, and neural-network approaches to increase accuracy. As a result, POS tagging continues to play a crucial role in the development of intelligent language technologies.